Direct polymerase chain reaction amplification of formalin-fixed, paraffin-wax-embedded tissue after automated sequential laser microdissection and pressure catapulting. Issue 2 (30th January 2007) - O'Kane, S L; Garimella, V; Sivarajasingham, N; Drew, P J; Cawkwell, L
Abstract : A robust method to facilitate rapid laser microdissection and pressure catapulting (LMPC) coupled with direct polymerase chain reaction (dPCR) to eliminate the need for extraction of DNA before a PCR-based assay is described. This sequential LMPC–dPCR method is rapid and decreases the number of processing steps, reducing the chance of tissue loss and contamination.